Health literacy and adherence to treatment of patients with heart failure - Monica Isabelle Lopes Oscalices; Meiry Fernanda Pinto Okuno; Maria Carolina Barbosa Teixeira Lopes; Ruth Ester Assayag Batista; Cassia Regina Vancini Campanharo
ABSTRACT Objective: To relate the level of functional health literacy with adherence and barriers to non-adherence, rehospitalization, readmission and death in patients with heart failure. Method: A cross-sectional, analytical study with patients admitted to the emergency room with a diagnosis of heart failure. Literacy was assessed by the Newest Vital Sign. Patient adherence to medication treatment and barriers to non-compliance were assessed 90 days after discharge by the Morisky-Green test and the Brief Medical Questionnaire, respectively. Results: 100 patients participated in the study. The mean age was 63.3 years (± 15.2), with a predominance of white women. Medication adherence was low in 41.1% of participants, of which 55.9% presented inadequate literacy. Re-hospitalization and death were present in patients with inadequate literacy (p<0.001). Conclusion: The low level of literacy was directly related to lower adherence and the presence of barriers to medication adherence, as well as higher rehospitalization rates and death.